Solvent-free acrylic adhesive composition and adhesive sheet
A solvent-free acrylic adhesive composition with a tailored monomer blend addresses the challenges of achieving both gasoline and alkali resistance, ensuring excellent adhesive properties and environmental sustainability.
Patent Information
- Application Number
- JP2024153321
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2044-03-15
AI Technical Summary
Existing acrylic adhesive compositions face challenges in achieving both excellent gasoline resistance and alkali resistance, while also ensuring environmental sustainability and safety, as they often require solvents, have poor stability, and limited crosslinking options.
A solvent-free acrylic pressure-sensitive adhesive composition is developed, comprising an acrylic partial copolymer with specific monomer ratios, including 85-93% (meth)acrylic acid ester with 4-8 carbon atoms in the alkyl group, 7-15% carboxyl group-containing monomer, and specific polymerizable monomers to enhance crosslinking and stability.
The composition achieves excellent adhesion, retention, constant load peeling force, gasoline resistance, and alkali resistance, while being environmentally friendly and safe for human use, contributing to sustainable development goals.
Smart Images

Figure 0007660953000001 
Figure 0007660953000002 
Figure 0007660953000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a solventless acrylic pressure-sensitive adhesive composition and a pressure-sensitive adhesive sheet. [Background technology]
[0002] The form of acrylic adhesives includes solvent-based acrylic adhesives, water-dispersed (emulsion-type) acrylic adhesives, and solvent-free acrylic adhesives (acrylic syrup). Of these, the solvent-based acrylic adhesives have been pointed out as having environmental hygiene and safety problems due to the solvent. In addition, water-dispersed (emulsion-type) acrylic adhesives have problems such as the need for a large amount of drying energy to evaporate the water medium, and the reduction in water resistance due to the inclusion of emulsifiers in the resulting coating film. On the other hand, solvent-free acrylic adhesives (acrylic syrup), especially ultraviolet-curing adhesives, are attracting attention because they are free of the problems caused by the solvent and can provide good adhesive performance. For this reason, various proposals have been made regarding ultraviolet-curing adhesives and adhesive products using them.
[0003] In general, acrylic pressure-sensitive adhesives are widely used in applications such as tapes, labels, stickers, and seals, and are excellent in weather resistance, durability, and high transparency. In addition, since there are a large number of monomer types that can be used for acrylic pressure-sensitive adhesives, acrylic pressure-sensitive adhesives are used in a wide variety of applications.
[0004] However, when acrylic adhesives are used for direct attachment to vehicles such as automobiles and motorcycles, detergents used for washing the car and gasoline used for refueling adhere to the acrylic adhesive, causing the general acrylic adhesive to dissolve or swell, which can cause problems such as the label attached to the vehicle with the acrylic adhesive peeling off.
[0005] For example, by using a copolymer of highly hydrophilic monomers such as acrylic acid alkyl ester monomers and carboxyl group-containing monomers, it is possible to improve the gasoline resistance of the acrylic adhesive, but the alkali resistance is deteriorated. If the content of the carboxyl group-containing monomer is reduced in order to reduce the hydrophilicity, the alkali resistance improves, but the gasoline resistance deteriorates, and the holding power and constant load peeling power deteriorate due to the decrease in cohesive force.
[0006] When lipophilic acrylic acid alkyl ester monomers are blended with acrylic adhesives, the alkali resistance improves, but the gasoline resistance deteriorates, and the cohesive strength decreases with the drop in the glass transition temperature of the polymer itself. In this way, it is difficult to achieve both gasoline resistance and alkali resistance by adjusting the lipophilicity and hydrophilicity through the blending balance of acrylic acid alkyl ester monomers and carboxyl group-containing monomers.
[0007] Therefore, Patent Documents 1 and 2 propose a solvent-based acrylic pressure-sensitive adhesive that uses a large amount of a carboxyl group-containing monomer and a hydroxyl group-containing monomer to achieve both gasoline resistance and alkali resistance required for an acrylic pressure-sensitive adhesive. To address the issue of reduced liquid stability due to hydrogen bonds formed by the carboxyl group-containing monomer and the hydroxyl group-containing monomer, the hydrogen bonds are inhibited by using an alcohol solvent, thereby achieving liquid stability.
[0008] Patent Document 3 proposes an acrylic resin composition in which the proportion of acrylate having alkylene glycol is 40 to 90% by mass and the proportion of units derived from carboxylic acid-containing (meth)acrylic monomer is 10 to 20% by mass. By increasing hydrophilicity, oil resistance (resistance to oleic acid, gasoline resistance, and toluene resistance) is enhanced.
[0009] Patent Document 4 proposes a water-dispersible pressure-sensitive adhesive that contains a water-dispersible polymer and inorganic particles in order to improve oil resistance, and that is characterized in that the content of the inorganic particles is 3 to 90 parts by mass per 100 parts by mass of the water-dispersible polymer. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] JP 2016-210863 A [Patent Document 2] JP 2019-189876 A [Patent Document 3] Patent Publication No. 2022-024067 [Patent Document 4] JP 2012-117053 A Summary of the Invention [Problem to be solved by the invention]
[0011] However, the manufacturing methods described in Patent Documents 1 and 2 cause environmental problems due to the emission of solvents, and are restricted in that they cannot use isocyanate-based crosslinking agents that react with the hydroxyl groups of alcohols. As a result, there are few options for crosslinking agents that can be used with solvent-based acrylic pressure-sensitive adhesives, which leads to problems such as poor adhesion to substrates.
[0012] In addition, in Patent Document 3, because the acrylic resin composition is highly hydrophilic, alkaline water easily penetrates the acrylic resin composition, causing the acrylic resin composition to swell and the coating film to peel off from the substrate or adherend. Therefore, the technology in Patent Document 3 cannot provide sufficient alkali resistance.
[0013] Furthermore, in Patent Document 4, separation of the water-dispersed polymer and the inorganic particles occurs, resulting in a problem of reduced solution stability of the pressure-sensitive adhesive.
[0014] Therefore, an object of the present invention is to provide a solventless acrylic pressure-sensitive adhesive composition which is excellent in adhesive strength, holding strength, constant-load peel strength, gasoline resistance, and alkali resistance. [Means for solving the problem]
[0015] In order to achieve the object of the present invention, the present invention has the following configuration: That is, a solventless acrylic pressure-sensitive adhesive composition, comprising an acrylic partial copolymer containing 85 to 93 parts by mass of (a) a (meth)acrylic acid ester having an alkyl group with 4 to 8 carbon atoms and 7 to 15 parts by mass of (b) a carboxyl group-containing acrylic monomer, and 0.10 to 1.5 parts by mass of (e) a polymerizable monomer having 2 or more alkylene glycols and 3 or more (meth)acryloyl groups in one molecule, and 0.03 to 0.40 parts by mass of (f) a polymerizable monomer having 1 or more functional groups reactive with active hydrogen groups and 1 or more (meth)acryloyl groups in one molecule, relative to 100 parts by mass of the acrylic partial copolymer. Department The polymerizable monomer (f) is 2-isocyanatoethyl methacrylate. Effect of the Invention
[0016] According to the present invention, it is possible to provide a solventless acrylic pressure-sensitive adhesive composition having excellent adhesive strength, holding strength, constant-load peel strength, gasoline resistance, and alkali resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The following embodiments are described in detail. Note that the following embodiments do not limit the scope of the invention, and not all of the combinations of features described in the embodiments are essential to the invention. Two or more of the features described in the embodiments may be combined in any combination.
[0018] In this specification, any numerical range specified using "to" is intended to include the numerical values before and after "to" as the lower and upper limit values of the range.
[0019] In this specification, the term "(meth)acrylic" means to include both the terms "acrylic" and "methacrylic". Similarly, the term "(meth)acrylate" means to include both the terms "acrylate" and "methacrylate". Examples of (meth)acrylic monomers include (meth)acrylic acid esters and (meth)acrylic acid. Of these, it is more preferable to use (meth)acrylic acid esters and (meth)acrylic acid, and it is even more preferable to use (meth)acrylic acid esters.
[0020] <Solvent-free acrylic adhesive composition> The solventless acrylic pressure-sensitive adhesive composition contains an acrylic partial copolymer containing 85 to 93 parts by mass of a (meth)acrylic acid ester (a) having an alkyl group with 4 to 8 carbon atoms and 7 to 15 parts by mass of a carboxyl group-containing acrylic monomer (b), and at least one of the following, relative to 100 parts by mass of the acrylic partial copolymer: 0.10 to 1.5 parts by mass of a polymerizable monomer (e) having two or more alkylene glycols and three or more (meth)acryloyl groups in one molecule; and 0.03 to 0.40 parts by mass of a polymerizable monomer (f) having one or more functional groups reactive with active hydrogen groups and one or more (meth)acryloyl groups in one molecule.
[0021] The solvent-free acrylic pressure-sensitive adhesive composition does not substantially contain a solvent. "Substantially not containing a solvent (e.g., an organic solvent)" means that an organic solvent is not actively blended into the solvent-free acrylic pressure-sensitive adhesive composition, except in cases where the organic solvent is inevitably mixed in. The solvent content of the solvent-free acrylic pressure-sensitive adhesive composition is preferably 2% by weight or less, more preferably 0 to 2% by weight, and even more preferably 0 to 1% by weight, based on 100% by weight of the solvent-free acrylic pressure-sensitive adhesive composition. If the solvent content is too high, air bubbles may be generated in the pressure-sensitive adhesive layer, and the durability of the pressure-sensitive adhesive sheet may decrease.
[0022] <Acrylic partial copolymer> The acrylic partial copolymer is a copolymer obtained by partially copolymerizing an acrylic monomer, and is also referred to as "acrylic syrup" in this specification. The advantages of the solventless acrylic pressure-sensitive adhesive composition containing acrylic syrup are as follows. For example, since the acrylic pressure-sensitive adhesive composition does not contain a solvent or water, it is not necessary to remove the solvent after application, so that the pressure-sensitive adhesive sheet can be obtained in a work process that is environmentally friendly and highly safe for the human body. In addition, it is possible to save a large amount of drying energy for evaporating water in the work process.
[0023] ((Meth)acrylic acid ester (a) having an alkyl group carbon number of 4 to 8) Examples of the (meth)acrylic acid ester (a) having an alkyl group with 4 to 8 carbon atoms include n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, sec-butyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, n-hexyl (meth)acrylate, heptyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. These monomers may be used alone or in combination of two or more. In particular, the (meth)acrylic acid ester (a) preferably contains at least one of butyl acrylate and 2-ethylhexyl acrylate.
[0024] Here, if a (meth)acrylic acid ester with an alkyl group having 3 or less carbon atoms is used, the glass transition temperature (Tg) of the polymer itself increases, and the cohesive strength increases, improving the retention and constant-load peel properties. On the other hand, the increased hydrophilicity reduces alkali resistance.
[0025] In addition, when a (meth)acrylic ester with an alkyl group having 9 or more carbon atoms is used, the lipophilicity increases, improving alkali resistance. On the other hand, the glass transition temperature (Tg) of the polymer itself decreases, decreasing the cohesive strength, resulting in poor retention and constant-load peel properties.
[0026] The content of the (meth)acrylic acid ester (a) having an alkyl group with 4 or more and 8 or less carbon atoms is 85 to 93 parts by mass in 100 parts by mass of all the monomers constituting the acrylic partial copolymer.
[0027] (Carboxyl group-containing acrylic monomer (b)) The amount of the carboxyl group-containing acrylic monomer (b) can impart cohesive strength to the solventless acrylic adhesive composition, and can adjust the adhesive strength, holding strength, and constant load peel properties. In addition, the incorporation of the carboxyl group-containing acrylic monomer (b) can increase the hydrophilicity of the acrylic adhesive composition, thereby improving the gasoline resistance.
[0028] Examples of the carboxyl group-containing acrylic monomer (b) include (meth)acrylic acid, monohydroxyethyl succinate (meth)acrylate, monohydroxyethyl phthalate (meth)acrylate, monohydroxyethyl hexahydrophthalate (meth)acrylate, monohydroxypropyl phthalate (meth)acrylate, β-carboxyethyl (meth)acrylate, and ω-carboxy-polycaprolactone mono(meth)acrylate. In the present invention, it is desirable to use at least one of these. Among these, it is preferable that the carboxyl group-containing acrylic monomer (b) contains acrylic acid, taking into consideration the copolymerizability with the above-mentioned (meth)acrylic acid ester (a) and the reactivity with the polymerizable monomer (f) described below.
[0029] The content of the carboxyl group-containing acrylic monomer (b) is 7 to 15 parts by mass in 100 parts by mass of all monomers constituting the acrylic partial copolymer. If the content of the carboxyl group-containing acrylic monomer (b) is less than 7 parts by mass, the following problems arise. For example, the hydrophilicity of the acrylic pressure-sensitive adhesive composition decreases, resulting in poor gasoline resistance, and the adhesive strength of the pressure-sensitive adhesive layer decreases, resulting in poor holding power and constant-load peeling properties. Thus, the pressure-sensitive adhesive layer cannot obtain sufficient adhesive performance. On the other hand, if the content of the carboxyl group-containing acrylic monomer (b) is more than 15 parts by mass, the hydrophilicity of the acrylic pressure-sensitive adhesive composition improves, resulting in improved gasoline resistance, but poor alkali resistance. Therefore, in order to achieve both gasoline resistance and alkali resistance, the amount of the carboxyl group-containing acrylic monomer (b) used is preferably 7 to 15 parts by mass.
[0030] (Hydroxyl-containing acrylic monomer (c)) The acrylic partial copolymer may further contain a hydroxyl group-containing acrylic monomer (c). The content of the hydroxyl group-containing acrylic monomer (c) is 7 parts by mass or less in 100 parts by mass of all monomers constituting the acrylic partial copolymer. When the hydroxyl group-containing acrylic monomer (c) is used in an amount of more than 7 parts by mass, the hydrophilicity of the acrylic pressure-sensitive adhesive composition increases, improving gasoline resistance, but the alkali resistance is deteriorated.
[0031] Examples of the hydroxyl group-containing acrylic monomer (c) include (meth)acrylic acid esters (hydroxyalkyl (meth)acrylates) having a hydroxyl group, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Among these, in consideration of the copolymerizability with the (meth)acrylic acid ester (a) and the reactivity with the polymerizable monomer (f) described below, it is preferable that the hydroxyl group-containing acrylic monomer (c) contains 4-hydroxybutyl acrylate.
[0032] By using these monomers alone, gasoline resistance can be improved without significantly decreasing alkali resistance. However, when the acrylic partial copolymer does not contain the carboxyl group-containing acrylic monomer (b) and contains the hydroxyl group-containing acrylic monomer (c), the adhesive strength and constant load peeling properties are poor, and the solventless acrylic pressure-sensitive adhesive composition cannot obtain sufficient adhesive properties. Therefore, when the acrylic partial copolymer contains the hydroxyl group-containing acrylic monomer (c), it is preferable to use the carboxyl group-containing acrylic monomer (b) and the hydroxyl group-containing acrylic monomer (c) in a mixed state. By using the carboxyl group-containing acrylic monomer (b) and the hydroxyl group-containing acrylic monomer (c) in a mixed state, the hydrophilicity of the acrylic pressure-sensitive adhesive composition can be improved, and therefore the gasoline resistance can be improved. In addition, the cohesive strength of the acrylic pressure-sensitive adhesive composition can be improved by hydrogen bonding between the carboxyl group and the hydroxyl group, and therefore the holding power and constant load peeling properties are improved.
[0033] <Polymerization method> The acrylic partial copolymer can be produced by ordinary solution polymerization, bulk polymerization, polymerization by irradiation with active energy rays, etc., but bulk polymerization in which polymerization is performed without using a solvent and active energy ray polymerization are preferred. Here, the active energy rays include ultraviolet rays. By using bulk polymerization or active energy ray polymerization, the acrylic partial copolymer can be obtained without going through a process such as desolvation, and can be used as it is in the production of the solventless acrylic pressure-sensitive adhesive composition of the present invention.
[0034] (Thermal polymerization initiator) Examples of the thermal polymerization initiator used in producing the acrylic partial copolymer include oil-soluble organic peroxides such as 2,4-dichlorobenzoyl peroxide, t-butyl peroxypivalate, dibenzoyl peroxide, bis(2-methylbenzoyl) peroxide, bis(3,5,5-trimethylhexanoyl) peroxide, dioctanoyl peroxide, t-butylperoxy-2-ethylhexanoate, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, dilauroyl peroxide, diisopropylbenzene hydroperoxide, t-butyl hydroperoxide, and di-t-butyl peroxide; and oil-soluble azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile). These may be used alone or in combination of two or more.
[0035] (Photopolymerization initiator (d)) In the present invention, a photopolymerization initiator (d) can be used when producing an acrylic partial copolymer and for the purpose of curing the polymerized acrylic adhesive composition with ultraviolet light. Representative photopolymerization initiators (d) include acetophenone-based, phosphine oxide-based, benzoin-based, benzophenone-based, and thioxanthone-based initiators. These are used alone or in combination of two or more.
[0036] Examples of the acetophenone-based initiator include acetophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-1,2-diphenylethan-1-one, 1-hydroxycyclohexyl phenyl ketone, and 2-hydroxy-2-methyl-1-phenylpropan-1-one.
[0037] Examples of the phosphine oxide initiator include bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0038] Examples of the benzoin-based initiator include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.
[0039] Examples of the benzophenone-based initiator include benzophenone, p-methoxybenzophenone, o-benzoylbenzoic acid, methyl o-benzoylbenzoate, 4,4'-bis(dimethylamino)benzophenone, and 4,4'-bis(diethylamino)benzophenone.
[0040] Examples of the thioxanthone initiator include thioxanthone, 2-methylthioxanthone, 2-isopropylthioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, and 2-chlorothioxanthone.
[0041] These initiators can be used alone or in combination of two or more. In the present invention, it is preferable to use an acetophenone-based initiator and / or a phosphine oxide-based initiator because of their good curability.
[0042] The solventless acrylic adhesive composition contains 0.3 to 1.0 parts by mass of photopolymerization initiator (d) relative to 100 parts by mass of acrylic partial copolymer. If the content of photopolymerization initiator (d) is less than 0.3 parts by mass, unreacted monomers are likely to remain, causing odor problems in the acrylic adhesive composition. On the other hand, if the content of photopolymerization initiator (d) is more than 1.0 part by mass, the molecular weight of the polymer (acrylic copolymer) after curing is low, and constant load peeling properties are poor.
[0043] (Chain transfer agent) In order to adjust the molecular weight of the acrylic partial copolymer, a chain transfer agent can be appropriately used. Examples of the chain transfer agent include mercaptans such as octyl thioglycolate, methoxybutyl thioglycolate, octyl mercaptopropionate, methoxybutyl mercaptopropionate, stearyl mercaptan, lauryl mercaptan, and α-methylstyrene dimer. These can be used alone or in combination of two or more.
[0044] <Additives> The solventless acrylic pressure-sensitive adhesive composition can contain at least one of the polymerizable monomer (e) and the polymerizable monomer (f).
[0045] For example, the solventless acrylic pressure-sensitive adhesive composition contains, per 100 parts by mass of the acrylic partial copolymer, at least one of: 0.10 to 1.5 parts by mass of a polymerizable monomer (e) having two or more alkylene glycols and three or more (meth)acryloyl groups in one molecule; and 0.03 to 0.40 parts by mass of a polymerizable monomer (f) having one or more functional groups reactive with active hydrogen groups and one or more (meth)acryloyl groups in one molecule.
[0046] (Polymerizable monomer (e)) The polymerizable monomer (e) is a monomer obtained by modifying a trifunctional or higher polyfunctional (meth)acrylate with an alkylene glycol. Examples of the alkylene oxide constituting the alkylene glycol include ethylene oxide, propylene oxide, butylene oxide, and isobutylene oxide, and preferably ethylene oxide and propylene oxide. The number of alkylene glycols contained in the polymerizable monomer (e) (represented by "n" in this specification) is 2 or more, and preferably 3 or more. The number of alkylene glycols contained in the polymerizable monomer (e) is 40 or less, and preferably 35 or less. The range of the number of alkylene glycols contained in the polymerizable monomer (e) is a combination of any upper limit value and lower limit value described above, and may be, for example, 2 or more and 40 or less, 2 or more and 35 or less, 3 or more and 40 or less, or 3 or more and 35 or less. The number of (meth)acryloyl groups contained in the polymerizable monomer (e) is preferably 3 or more and 5 or less, and more preferably 3 or more and 4 or less. Examples of the polymerizable monomer (e) include trimethylolpropane EO-modified (n ≒ 3, 20) tri(meth)acrylate, trimethylolpropane PO-modified tri(meth)acrylate, isocyanuric acid EO-modified triacrylate, and pentaerythritol EO-modified (n ≒ 35) tri- and tetra(meth)acrylate. In the present invention, it is desirable to use at least one of these. Cohesive strength can be imparted by adding a polymerizable monomer (e) together with a photopolymerization initiator (d) to the solvent-free acrylic adhesive composition of the present invention and crosslinking it. Furthermore, the addition of alkylene glycol to the crosslinked portion improves hydrophilicity and improves gasoline resistance.
[0047] The content of the polymerizable monomer (e) is 0.10 to 1.5 parts by mass, preferably 0.15 to 1.5 parts by mass, based on 100 parts by mass of the acrylic partial copolymer. If the content of the polymerizable monomer (e) is less than 0.10 parts by mass, the gel fraction of the adhesive layer decreases, and sufficient cohesive strength cannot be obtained. As a result, the holding power of the adhesive layer deteriorates, and the gasoline resistance does not improve. On the other hand, if the content of the polymerizable monomer (e) is more than 1.5 parts by mass, the cohesive strength of the acrylic adhesive composition increases too much, causing a loss of flexibility, and thus deteriorating the constant load peeling properties.
[0048] (Polymerizable monomer (f)) The polymerizable monomer (f) is a monomer having one or more isocyanate groups and one or more (meth)acryloyl groups. Here, the number of isocyanate groups is 1 to 3, preferably 1. The number of (meth)acryloyl groups is 1 to 3, preferably 1 to 2. An example of the polymerizable monomer (f) having one isocyanate group and one (meth)acryloyl group is 2-isocyanatoethyl (meth)acrylate. An example of the polymerizable monomer (f) having one isocyanate group and two (meth)acryloyl groups is 1,1-(bis(meth)acryloyloxymethyl)ethyl isocyanate, from the viewpoint of further enhancing the ultraviolet curing property. Commercially available polymerizable monomers (f) include 2-isocyanatoethyl acrylate (trade name: Karenz AOI, manufactured by Resonac Corporation), 2-isocyanatoethyl methacrylate (trade name: Karenz MOI, manufactured by Resonac Corporation), and 1,1-bis(acryloyloxymethyl)ethyl isocyanate (trade name: Karenz BEI, manufactured by Resonac Corporation).
[0049] In addition, "Karenz MOI-BM" (manufactured by Resonac) in which the isocyanate group of 2-isocyanatoethyl methacrylate is blocked with an amine compound, "Karenz MOI-BP" (manufactured by Resonac) in which it is blocked with a pyrazole compound, a polymer of 2-hydroxyethyl acrylate (HEA) and 1,6-diisocyanatohexane (HDI) (product name "Laromer PR9000" manufactured by BASF), glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, etc. can also be used as the polymerizable monomer (f).
[0050] In the present invention, in consideration of reactivity with active hydrogen groups, it is preferable that the polymerizable monomer (f) contains at least one of 2-isocyanatoethyl acrylate (trade name: Karenz AOI, manufactured by Resonac Co., Ltd.) and 2-isocyanatoethyl methacrylate (trade name: Karenz MOI, manufactured by Resonac Co., Ltd.).
[0051] In the present invention, the polymerizable monomer (f) provides a functional group that reacts with an active hydrogen group to the acrylic polymer that is photopolymerized during UV curing. Meanwhile, the components of the acrylic partial copolymer of the present invention include active hydrogen group-containing monomers such as the carboxyl group-containing acrylic monomer (b) and the hydroxyl group-containing acrylic monomer (c). Therefore, active hydrogen groups such as carboxyl groups and hydroxyl groups are also provided to the acrylic polymer in the acrylic partial copolymer and the acrylic polymer that is photopolymerized during UV curing. The functional group that reacts with the active hydrogen group reacts with the active hydrogen group during curing, and the active hydrogen group such as the carboxyl group and hydroxyl group, introduces a crosslinking structure into the acrylic polymer that contributes to the formation of the adhesive.
[0052] Here, the functional group that reacts with one or more active hydrogen groups in one molecule of the polymerizable monomer (f) is an isocyanate group. The number of functional groups that react with one or more active hydrogen groups in one molecule of the polymerizable monomer (f) is 1 to 3, and preferably 1.
[0053] An acrylic partial copolymer containing an acrylic polymer having a carbon-carbon double bond can also be obtained by reacting in advance a functional group that reacts with one or more active hydrogen groups in one molecule of the polymerizable monomer (f) with an active hydrogen group such as a carboxyl group or a hydroxyl group of the acrylic polymer in the acrylic partial copolymer. In this case, a heating step at about 40 to 80°C is required in a reaction vessel, for example. In order to avoid the heating step, in the present invention, it is preferable to react the polymerizable monomer (f) with the acrylic polymer in the acrylic partial copolymer in the ultraviolet curing step and the curing step as described above, without reacting the polymerizable monomer (f) with the acrylic polymer in the acrylic partial copolymer in advance.
[0054] The content of the polymerizable monomer (f) is 0.03 to 0.40 parts by mass relative to 100 parts by mass of the acrylic partial copolymer. If the content of the polymerizable monomer (f) is less than 0.03 parts by mass, the gel fraction of the adhesive layer is reduced and the cohesive strength is insufficient, resulting in poor holding power and constant-load peeling properties of the adhesive layer. Therefore, the adhesive layer cannot obtain sufficient adhesive performance. On the other hand, if the content of the polymerizable monomer (f) is more than 0.40 parts by mass, the cohesive strength of the acrylic adhesive composition increases too much, resulting in loss of flexibility, resulting in poor constant-load peeling properties.
[0055] <Other additives> The solventless acrylic pressure-sensitive adhesive composition may contain various additives as necessary within the range that does not inhibit the adhesive performance of the pressure-sensitive adhesive sheet. Examples of other additives include antioxidants, ultraviolet absorbers, fillers, pigments, thickeners, antistatic agents, silane coupling agents, flame retardants, and tackifier resins. These are used alone or in combination of two or more.
[0056] <Application> The solvent-free acrylic adhesive composition of the present invention is cured by irradiation with active energy rays (e.g., ultraviolet rays), so that thick coating is possible. The solvent-free acrylic adhesive composition of the present invention is for marking films. The adhesive using the solvent-free acrylic adhesive composition of the present invention is used, for example, as an adhesive for marking films. The marking film is a sheet material with an adhesive. A general method of using the marking film will be described. First, a user cuts a marking film (sheet material) to obtain a sheet with a desired shape of characters, logos, etc., in order to display, decorate, and advertise the name and business hours, etc., of a store owned by the user or another person. Then, the user sticks the marking film cut into a desired shape, for example, to a signboard and glass, etc., inside and / or outside the store. Alternatively, the user can directly stick a marking film of the user's desired shape to the painted surface of a vehicle, etc., for the purpose of improving the design of a vehicle such as a motorcycle or automobile. This improves the aesthetics of the vehicle, etc., and satisfies the user's various preferences for vehicles.
[0057] The marking film has a substrate made of a synthetic resin film such as polyvinyl chloride (PVC), polyurethane, polyester, or polystyrene. One side of the substrate is colored or printed. An adhesive is applied to the other side of the substrate. From the viewpoints of weather resistance, colorability, and cost advantage, it is preferable to use a PVC film as the substrate. When using a PVC film, it may be plasticized with a polymer plasticizer or the like to prevent the plasticizer in the PVC film from migrating to the adhesive and softening the film.
[0058] <Adhesive sheet> The pressure-sensitive adhesive sheet of the present invention comprises a substrate and a pressure-sensitive adhesive layer made of a solvent-free acrylic pressure-sensitive adhesive composition provided on at least one surface of the substrate. The pressure-sensitive adhesive layer is formed by curing the solvent-free acrylic pressure-sensitive adhesive composition using active energy rays. The pressure-sensitive adhesive sheet can be used in combination with the pressure-sensitive adhesive described above, and can be used for the same purpose as the pressure-sensitive adhesive. The pressure-sensitive adhesive layer and the pressure-sensitive adhesive sheet can be formed by the method described below.
[0059] Here, the gel fraction of the pressure-sensitive adhesive layer is 37 to 75%. The method for measuring the gel fraction will be described in Test 7 below. For example, when the gel fraction is less than 37%, the acrylic pressure-sensitive adhesive composition does not have sufficient cohesive strength, so that the holding power of the pressure-sensitive adhesive layer deteriorates and gasoline resistance does not improve. On the other hand, when the gel fraction exceeds 75%, the cohesive strength of the acrylic pressure-sensitive adhesive composition increases too much, so that the flexibility of the pressure-sensitive adhesive layer is impaired and the constant-load peel property deteriorates.
[0060] <Method of manufacturing acrylic syrups A to J> Table 1 shows the raw material composition and physical properties of acrylic syrup. Based on the raw material composition of acrylic syrup A in Table 1, a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube was charged with nitrogen gas, and then 90 parts of butyl acrylate (BA), 10 parts of acrylic acid (AAC), and 0.005 parts of a thermal polymerization initiator (2,2'-azobisisobutyronitrile) were charged. While stirring, the mixture was reacted at 85°C for 5 hours in a nitrogen gas stream. After the reaction was completed, the mixture was diluted with monomers of the same composition ratio to obtain acrylic syrup A with an evaporation residue of 30.4% by mass. The viscosity of acrylic syrup A was measured using a viscometer (manufactured by Toki Sangyo Co., Ltd., device name: B-type viscometer). Acrylic syrups B to J were obtained in the same process as acrylic syrup A based on the raw material composition in Table 1, and detailed explanations will be omitted.
[0061] [Table 1] (remarks) ·BA: Butyl acrylate 2EHA: 2-Ethylhexyl acrylate AAC: Acrylic acid 4HBA: 4-Hydroxybutyl acrylate
[0062] <Method for producing a solventless acrylic pressure-sensitive adhesive composition containing a polymerizable monomer (e)> Table 2 shows the raw material blends of the solventless acrylic pressure-sensitive adhesive compositions of Examples 1 to 8 and Comparative Examples 1 to 6. Based on the raw material blend of Example 1 in Table 2, 0.5 parts of Aronix M-350 (trade name, manufactured by Toagosei Co., Ltd.) as the polymerizable monomer (e) and 1.0 part of Omnirad651 (trade name, manufactured by IGM Resins Co., Ltd.) as the photopolymerization initiator (d) were added to 100 parts of acrylic syrup A and thoroughly mixed to obtain the solventless acrylic pressure-sensitive adhesive composition of Example 1. The solventless acrylic pressure-sensitive adhesive compositions of Examples 2 to 8 and Comparative Examples 1 to 6 were obtained by the same process as in Example 1 based on the raw material blends in Table 2, and therefore detailed explanations are omitted.
[0063] [Table 2] (remarks) <Polymerizable monomer (e)> A: Trimethylolpropane EO modified (n≒3) triacrylate (Aronix M-350 / manufactured by Toagosei Co., Ltd.) B: Trimethylolpropane EO modified (n≒20) triacrylate (NK Ester AT-20E / Shin-Nakamura Chemical Co., Ltd.) C: Pentaerythritol EO-modified (n ≒ 35) tri- and tetraacrylate (NK Ester ATM-35E / Shin-Nakamura Chemical Co., Ltd.) D: Trimethylolpropane triacrylate (Aronix M-309 / manufactured by Toagosei Co., Ltd.) The numerical value of "n" above is the number of polyalkylene glycols contained in the polymerizable monomer (e). <Photopolymerization initiator (d)> A: 2,2-dimethoxy-1,2-diphenylethan-1-one (Omnirad651 / IGM Resins) B: 1-hydroxycyclohexyl phenyl ketone (Omnirad184 / IGM Resins) C: Bis(2,4,6-trimethylbenzoyl)-phenylphosphineside (Omnirad819 / IGM Resins) D: 2,4,6-trimethylbenzoyl-diphenyl-phosphinoxide (Omnirad TPO / IGM Resins)
[0064] <Method for producing a solventless acrylic pressure-sensitive adhesive composition containing a polymerizable monomer (f)> Table 3 shows the raw material blends of the solventless acrylic pressure-sensitive adhesive compositions of Examples 9 to 18 and Comparative Examples 7 to 12. Based on the raw material blend of Example 9 in Table 3, 0.40 parts of Karenz MOI (trade name, manufactured by Resonac) as the polymerizable monomer (f) and 1.0 part of Omnirad651 (trade name, manufactured by IGM Resins) as the photopolymerization initiator (d) were added to 100 parts of acrylic syrup A and thoroughly mixed to obtain the solventless acrylic pressure-sensitive adhesive composition of Example 9. The solventless acrylic pressure-sensitive adhesive compositions of Examples 10 to 18 and Comparative Examples 7 to 12 were obtained by the same process as in Example 9 based on the raw material blends in Table 3, and therefore detailed explanations are omitted.
[0065] [Table 3] (remarks) <Polymerizable monomer (f)> A: 2-isocyanatoethyl methacrylate (Karenz MOI / Resonac) B: 2-isocyanatoethyl acrylate (Karenz AOI / Resonac) <Photopolymerization initiator (d)> A: 2,2-dimethoxy-1,2-diphenylethan-1-one (Omnirad651 / IGM Resins) B: 1-hydroxycyclohexyl phenyl ketone (Omnirad184 / IGM Resins) C: Bis(2,4,6-trimethylbenzoyl)-phenylphosphineside (Omnirad819 / IGM Resins) D: 2,4,6-trimethylbenzoyl-diphenyl-phosphinoxide (Omnirad TPO / IGM Resins)
[0066] <Method for producing a solventless acrylic pressure-sensitive adhesive composition containing polymerizable monomer (e) and polymerizable monomer (f)> Table 4 shows the raw material blends of the solventless acrylic adhesive compositions of Examples 19 to 27 and Comparative Examples 13 to 16. Based on the raw material blend of Example 19 in Table 4, 0.5 parts of NK Ester AT-20E (trade name, manufactured by Shin-Nakamura Chemical Co., Ltd.) as the polymerizable monomer (e), 0.08 parts of Karenz MOI (trade name, manufactured by Resonac Co., Ltd.) as the polymerizable monomer (f), and 0.3 parts of Omnirad651 (trade name, manufactured by IGM Resins Co., Ltd.) as the photopolymerization initiator (d) were added to 100 parts of acrylic syrup B, and thoroughly mixed to obtain the solventless acrylic adhesive composition of Example 19. The solventless acrylic adhesive compositions of Examples 20 to 27 and Comparative Examples 13 to 16 were obtained by the same process as Example 19 based on the raw material blends in Table 4, and detailed explanations will be omitted.
[0067] [Table 4] (remarks) The notes are the same as those in Tables 2 and 3 and are therefore omitted.
[0068] <Creating adhesive sheets for evaluation> The following evaluation adhesive sheets were prepared using the respective solvent-free acrylic adhesive compositions of Examples 1 to 27 and Comparative Examples 1 to 16. The respective solvent-free acrylic adhesive compositions of Examples 1 to 27 and Comparative Examples 1 to 16 were used to form an adhesive layer having a thickness of 25 μm on a PVC film by the following method, to prepare an adhesive sheet. Each solvent-free acrylic adhesive composition was applied onto a silicone resin-coated PET film (heavy release type releasable substrate), and then a PET film (light release type releasable substrate) was attached thereto, and the composition was cured by irradiating ultraviolet light under the following ultraviolet curing conditions. After curing, the PET film (light release type releasable substrate) was peeled off, and the adhesive layer on the PET film (heavy release type releasable substrate) was transferred to the PVC film, and the composition was aged for 5 days in an environment of 23° C. and 50% RH, to obtain an evaluation adhesive sheet. The ultraviolet curing conditions were an illuminance of 172 mW / cm using a metal halide lamp. 2 , Accumulated light intensity 1550mJ / cm 2 The irradiation conditions at 1000 ℃ were included. The UV POWER PUCK manufactured by EIT was used as the illuminance and light intensity meter.
[0069] <Methods for evaluating the properties of adhesives and adhesive sheets> (Test 1: Measurement of adhesive strength) For each adhesive sheet, the 180° peel adhesion to a test plate (melamine-coated plate) was measured in an environment of 23°C and 50% RH according to JIS Z0237. Specifically, the adhesive sheet was cut to a width of 25 mm, attached to a melamine-coated plate, and pressed once back and forth with a pressing roll under a load of 2 kg to prepare a test piece for measuring the adhesion to the melamine-coated plate. After being left for 48 hours in an environment of 23°C and 50% RH after pressing, the adhesive sheet was peeled off at a peel speed of 300 mm / min to measure the adhesion to the melamine-coated plate. The adhesive strength of the adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: Adhesive strength is 13.0N / 25mm or more Fail: Adhesive strength is less than 13.0N / 25mm
[0070] (Test 2: Measurement of holding power) Each adhesive sheet was cut to a size of 25 mm wide and 50 mm long to prepare a test piece for measuring the holding power. This test piece was attached to a SUS plate so that the adhesive area was 25 mm x 25 mm according to JIS Z0237, and pressed once with a pressure roller under a load of 2 kg. After that, it was left in an environment of 23 ° C and 50% RH for 60 minutes, and then left in an environment of 40 ° C for 20 minutes, after which a weight of 1.0 kg was attached including a hook for attaching the weight, and the distance of the test piece that had shifted after 24 hours (shift length; mm) or the time it took for the test piece to completely peel off (fall time; minutes) was measured. The holding power of the adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: The deviation length is 0.5 mm or less Fail: The slippage exceeds 0.5 mm or the test piece falls within 24 hours of holding time.
[0071] (Test 3: Measurement of constant load peel strength (melamine-coated plate)) Each adhesive sheet was cut to a size of 25 mm wide and 70 mm long to prepare a test piece for measuring the constant load peeling force. The test piece was attached to a melamine-coated plate so that the adhesive area was 25 mm x 50 mm, and was pressed back and forth once with a pressure roller under a load of 2 kg. After that, it was left in an environment of 23 ° C and 50% RH for 60 minutes, and then the pressed tape sample was set in a dedicated jig in an environment of 23 ° C and 50% RH, and a 0.20 kg weight was attached to the end of the tape sample to be evaluated, including a hook for attaching the weight, so that a load for peeling in a 90 ° direction relative to the adhesive surface was applied. The peeling distance (peel length; mm) of the test piece after 120 minutes, or the time when the test piece completely peeled off (fall time; minutes) was measured. The constant load peeling force of the adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: Peel length is 40.0 mm or less Fail: The peel length exceeds 40.0 mm, or the test piece falls within 120 minutes of holding time.
[0072] (Test 4: Measurement of constant load peel strength (polypropylene (PP) plate)) Each adhesive sheet was cut to a size of 25 mm wide and 70 mm long to prepare a test piece for measuring the constant load peeling force. The test piece was attached to a polypropylene (PP) plate so that the adhesive area was 25 mm x 50 mm, and was pressed back and forth once with a pressure roller under a load of 2 kg. After that, it was left in an environment of 23 ° C and 50% RH for 60 minutes, and then in an environment of 40 ° C, the pressed tape sample was set in a dedicated jig, and a weight of 0.05 kg was attached to the end of the tape sample to be evaluated, including a hook for attaching the weight, so that a load for peeling in a 90 ° direction relative to the adhesive surface was applied. The peeling distance (peel length; mm) of the test piece after 120 minutes, or the time when the test piece completely peeled off (fall time; minutes) was measured. The constant load peeling force of the adhesive sheet was evaluated based on the following evaluation criteria. (Evaluation Criteria) Pass: Peel length is 40.0 mm or less Fail: The peel length exceeds 40.0 mm, or the test piece falls within 120 minutes of holding time.
[0073] (Test 5: Evaluation of gasoline resistance) Each adhesive sheet was cut to a size of 20 mm x 50 mm to prepare a test piece for the gasoline resistance test. Each test piece was attached to a melamine-coated plate and left for 24 hours in an environment of 23°C and 50% RH, then immersed in simulated gasoline (a 1:1 mixed solution of toluene and isooctane) for 30 minutes, and after 24 hours, the sample attached to the melamine-coated plate was visually observed for changes in appearance and evaluated according to the following criteria. In this case, ○ indicates that there is no problem in practical use. △ and × indicate that it is not suitable for practical use. (Evaluation Criteria) ○: No change, or wrinkles appear on the PVC film after removal, but it returns to its original state after 24 hours △: PVC film wrinkled and slightly peeled off ×: The PVC film is deformed by wrinkles, swelling, shrinkage, etc., resulting in poor appearance.
[0074] (Test 6: Evaluation of Alkaline Resistance) Each adhesive sheet was cut to a size of 20 mm x 50 mm to prepare a test piece for the alkali resistance test. Each test piece was attached to a melamine-coated plate and left for 24 hours in an environment of 23°C and 50% RH, then immersed in a 0.1N sodium hydroxide aqueous solution for 7 hours. After removal, the sample attached to the melamine-coated plate was visually observed for changes in appearance after 24 hours and evaluated according to the following criteria. In this case, ○ indicates that there is no problem in practical use. △ and × indicate that it is not suitable for practical use. (Evaluation Criteria) ○: No change, or the adhesive layer swells after removal, but returns to its original state after 24 hours △: The adhesive layer swells and does not return to its original state. ×: The adhesive layer was changed by swelling, dissolution, etc.
[0075] (Test 7: Measurement of gel fraction) After UV curing, the adhesive film was cured for 5 days in an environment of 23°C and 50% RH, and 0.1 g of the resulting adhesive film was accurately weighed (W1) and immersed in 50 ml of ethyl acetate for 1 day. The weighed 200 mesh wire mesh (W2) was used for filtration to extract the soluble matter. The 200 mesh wire mesh used for filtration was then dried. The weight of the dried 200 mesh wire mesh (W3) was then weighed. The gel fraction (wt%) was calculated from these measured values using the following formula. Gel fraction (weight%) = ((W3-W2) / W1) x 100 W1: Weight of adhesive coating W2: Weight of 200 mesh wire netting W3: Weight of 200 mesh wire netting after drying
[0076] (Test Results) Table 2 shows the test results of Examples 1 to 8 and Comparative Examples 1 to 6. Table 3 shows the test results of Examples 9 to 18 and Comparative Examples 7 to 12. Table 4 shows the test results of Examples 19 to 27 and Comparative Examples 13 to 16.
[0077] (Test results of Examples 1 to 27) According to Tables 2 to 4, Examples 1 to 27 have excellent properties in all of adhesive strength, holding strength, constant load peel strength, gasoline resistance, and alkali resistance.
[0078] (Test results for Comparative Examples 1 to 16) On the other hand, Comparative Examples 1 to 16 did not have excellent properties in any of adhesive strength, holding strength, constant-load peel strength, gasoline resistance, and alkali resistance. Hereinafter, adhesive strength, holding strength, constant-load peel strength, gasoline resistance, and alkali resistance are collectively referred to as "required performance."
[0079] (Consideration of Test Results of Comparative Examples 1 to 6) Comparative Example 1 does not meet the required performance because it contains a polymerizable monomer that does not have an alkylene glycol. Comparative Example 2 does not meet the required performance because it contains a polymerizable monomer (e) that exceeds the blending amount specified in the present invention and a photopolymerization initiator (d) that exceeds the blending amount specified in the present invention. Comparative Example 3 does not meet the required performance because it contains a polymerizable monomer (e) that is less than the blending amount specified in the present invention. Comparative Example 4 does not meet the required performance because it contains a carboxyl group-containing acrylic monomer (b) that exceeds the blending amount specified in the present invention. Comparative Example 5 does not meet the required performance because it contains a carboxyl group-containing acrylic monomer (b) that is less than the blending amount specified in the present invention and the gel fraction is less than the range specified in the present invention. Comparative Example 6 does not meet the required performance because the gel fraction is less than the range specified in the present invention.
[0080] (Consideration of the test results of Comparative Examples 7 to 12) Comparative Example 7 does not meet the required performance because it contains less than the blending amount of polymerizable monomer (f) specified in the present invention. Comparative Example 8 does not meet the required performance because it contains more than the blending amount of polymerizable monomer (f) specified in the present invention. Comparative Example 9 does not meet the required performance because the gel fraction is less than the range specified in the present invention. Comparative Example 10 does not meet the required performance because it contains less than the blending amount of carboxyl group-containing acrylic monomer (b) specified in the present invention. Comparative Example 11 does not meet the required performance because it contains more than the blending amount of carboxyl group-containing acrylic monomer (b) specified in the present invention. Comparative Example 12 does not meet the required performance because it contains more than the blending amount of hydroxyl group-containing acrylic monomer (c) specified in the present invention.
[0081] (Consideration of the test results of Comparative Examples 13 to 16) Comparative Example 13 contains a polymerizable monomer (e) that does not have an alkylene glycol, and therefore does not meet the required performance. Comparative Example 14 contains a polymerizable monomer (e) that is less than the blending amount specified in the present invention, and therefore does not meet the required performance. Comparative Example 15 contains a polymerizable monomer (e) that exceeds the blending amount specified in the present invention, and therefore does not meet the required performance. Comparative Example 16 contains a polymerizable monomer (f) and a photopolymerization initiator (d) that exceed the blending amounts specified in the present invention, and therefore does not meet the required performance.
[0082] As described above, the solventless acrylic pressure-sensitive adhesive composition of the present invention has remarkable effects such as excellent adhesive strength, holding strength, constant-load peel strength, gasoline resistance, and alkali resistance.
[0083] Furthermore, the present invention can provide a solvent-free acrylic pressure-sensitive adhesive composition that is environmentally friendly and highly safe for the human body, making it possible to contribute to the achievement of Goal 12 of the Sustainable Development Goals (SDGs) led by the United Nations, "Responsible Consumption and Production."
[0084] The invention is not limited to the above-described embodiment, and various modifications and variations are possible within the scope of the gist of the invention.
Claims
1. A solvent-free acrylic pressure-sensitive adhesive composition comprising: an acrylic partial copolymer containing 85 to 93 parts by mass of a (meth)acrylic acid ester (a) having an alkyl group with 4 to 8 carbon atoms and 7 to 15 parts by mass of a carboxyl group-containing acrylic monomer (b); The copolymer contains, relative to 100 parts by mass of the acrylic partial copolymer, 0.10 to 1.5 parts by mass of a polymerizable monomer (e) having two or more alkylene glycols and three or more (meth)acryloyl groups in one molecule, and 0.03 to 0.40 parts by mass of a polymerizable monomer (f) having one or more functional groups reactive with active hydrogen groups and one or more (meth)acryloyl groups in one molecule; The polymerizable monomer (f) is 2-isocyanatoethyl methacrylate. A solvent-free acrylic pressure-sensitive adhesive composition.
2. A solventless acrylic pressure-sensitive adhesive composition, an acrylic partial copolymer containing 85 to 93 parts by mass of a (meth)acrylic acid ester (a) having an alkyl group with 4 to 8 carbon atoms and 7 to 15 parts by mass of a carboxyl group-containing acrylic monomer (b); The acrylic partial copolymer contains 0.10 to 1.5 parts by mass of a polymerizable monomer (e) having two or more alkylene glycols and three or more (meth)acryloyl groups in one molecule, based on 100 parts by mass of the acrylic partial copolymer. A solvent-free acrylic pressure-sensitive adhesive composition.
3. The polymerizable monomer (e) includes at least one of trimethylolpropane EO-modified (n ≒ 3, 20) tri(meth)acrylate, trimethylolpropane PO-modified tri(meth)acrylate, isocyanuric acid EO-modified triacrylate, and pentaerythritol EO-modified (n ≒ 35) tri- and tetra(meth)acrylate, The solventless acrylic pressure-sensitive adhesive composition according to claim 1 or 2.
4. Further comprising a photopolymerization initiator (d), The photopolymerization initiator (d) is contained in an amount of 0.3 to 1.0 part by mass relative to 100 parts by mass of the acrylic partial copolymer. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 or 2.
5. The (meth)acrylic acid ester (a) is butyl acrylate, The carboxyl group-containing acrylic monomer (b) is acrylic acid. The solventless acrylic pressure-sensitive adhesive composition according to claim 1 or 2.
6. For marking film, The solventless acrylic pressure-sensitive adhesive composition according to claim 1 or 2.
7. A substrate; and a pressure-sensitive adhesive layer comprising the solventless acrylic pressure-sensitive adhesive composition according to claim 1 or 2, the pressure-sensitive adhesive layer being provided on at least one surface of the substrate. Adhesive sheet.
8. The pressure-sensitive adhesive layer is formed by curing the solvent-free acrylic pressure-sensitive adhesive composition using active energy rays. The pressure-sensitive adhesive sheet according to claim 7.
9. The active energy rays include ultraviolet rays. The pressure-sensitive adhesive sheet according to claim 8.
Citation Information
Patent Citations
JP1975087414A
Water-dispersible oil-resistant adhesive composition, oil-resistant adhesive sheet, adhesion method, and oil-resistant adhesive structure
JP2012117053A
Adhesive composition for marking film, manufacturing method therefor and marking film
JP2016210863A
Acrylic pressure-sensitive adhesive, method for production thereof, and marking film
JP2018024717A
Adhesive sheet
JP2019070078A